Paper-based supercapacitor with screen-printed poly (3, 4-ethylene dioxythiophene)-poly (styrene sulfonate)/multiwall carbon nanotube films actuating both as electrodes and current collectors - Klem, Maykel dos Santos [UNESP] (2019)
Here we describe a screen-printed supercapacitor produced onto filter paper using poly (3, 4-ethylene dioxythiophene)-poly (styrene sulfonate) (PEDOT:PSS)/multiwall carbon nanotube (MWCNT) composite as active materials. We use a gel-like electrolyte based on poly (vinyl alcohol) and phosphoric acid (PVA/H3PO4), serving as both an ionic conductor and as an electrode separator. The electrodes are physically characterized through micro-Raman scattering analyses, sheet resistance measurements as a function of the printed number of layers and through scanning electron microscopy. The supercapacitor performance is investigated through impedance spectroscopy, equivalent circuit fitting, cyclic voltammetry (CV), long-term cycle stability and galvanostatic charge/discharge. The electrodes exhibit a low sheet resistance, reaching 17 Ω sq−1, being suitable for use as both electrode and the current collector. The supercapacitor shows good capability behavior over impedance spectroscopy and CV measurements, and 72% of capacitance retention after 1000 cycles. We find a maximum specific capacitance of 20,3 F g−1 for a charge/discharge current of 1 mA, and equivalent series resistance of 60 Ω leading to energy and power densities of 3,1 Wh kg−1 and 420 W kg−1, respectively. In conclusion, we describe here a flexible supercapacitor without metal collectors produced by a simple printing method.